MR and CT imaging in the Dyke-Davidoff-Masson syndrome: report of three cases and contribution to pathogenesis and differential diagnosis - PAULO HENRIQUE AGUIAR; WEI LIU CHING; HELIO LEITÃO; F. ISSA; GUILHERME LEPSKI; EBERVAL GADELHA FIGUEIREDO; FERNANDO GOMES-PINTO; RAUL MARINO JR (Arquivos de Neuro-Psiquiatria)
Cerebral hemiatrophy or Dyke-Davidoff-Masson syndrome is a condition characterized by seizures, facial asymmetry, contralateral hemiplegia or hemiparesis, and mental retardation. These findings are due to cerebral injury that may occur early in life or in utero. The radiological features are unilateral loss of cerebral volume and associated compensatory bone alterations in the calvarium, like thickening, hyperpneumatization of the paranasal sinuses and mastoid cells and elevation of the petrous ridge. The authors describe three cases. Classical findings of the syndrome are present in variable degrees according to the extent of the brain injury. Pathogenesis is commented.